2019
DOI: 10.3389/fneur.2019.00735
|View full text |Cite
|
Sign up to set email alerts
|

Routine Cerebrospinal Fluid Cytology Reveals Unique Inclusions in Macrophages During Treatment With Nusinersen

Abstract: Background: Spinal muscular atrophy (SMA) is an autosomal recessive neurodegenerative disorder characterized by degeneration of spinal motor neurons leading to muscular weakness. The antisense oligonucleotide nusinersen was approved for the treatment of patients with 5q-associated SMA. Treatment must be repeatedly administered intrathecally by lumbar puncture. So far, data regarding cerebrospinal fluid (CSF) parameters are sparse and examinations of CSF cytology during nusinersen treatment are compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 14 publications
3
16
0
1
Order By: Relevance
“…Here, we present a non‐targeted, control‐matched CSF proteomic analysis in adult patients with later‐onset SMA in correlation with clinical outcome, immediately before (T 0 ) and 10 months after initiation of nusinersen treatment (T 10 ), along with changes in basic CSF parameters (Figure a). Concordant with recent findings from another group (Gingele et al, ), we observed a higher number of reactive mononuclear cells in CSF of nusinersen‐treated patients compared with baseline and controls (Table ). We also found a consistent increase in CSF total protein (Table ; Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Here, we present a non‐targeted, control‐matched CSF proteomic analysis in adult patients with later‐onset SMA in correlation with clinical outcome, immediately before (T 0 ) and 10 months after initiation of nusinersen treatment (T 10 ), along with changes in basic CSF parameters (Figure a). Concordant with recent findings from another group (Gingele et al, ), we observed a higher number of reactive mononuclear cells in CSF of nusinersen‐treated patients compared with baseline and controls (Table ). We also found a consistent increase in CSF total protein (Table ; Fig.…”
Section: Discussionsupporting
confidence: 92%
“…However, this increase did not reach the level of significance in our patient cohort ( p = .07). A recent study detected reactive immune cells in the CSF of nusinersen‐treated patients (Gingele et al, ). In our cohort, 2/10 SMA patients had few activated lymphocytes in the CSF at T 0 and 6/10 patients had mononuclear and/or phagocytic cells at T 10 .…”
Section: Resultsmentioning
confidence: 99%
“…6 As nusinersen is administered intrathecally, a recent study examined the cerebrospinal fluid (CSF) of patients for any adverse effects. 7 The investigators noted macrophages with bizarre inclusions without clear inflammatory sequelae or adverse effects. Here, we report two cases with similar CSF findings.…”
Section: Unusual Inclusions In Cerebrospinal Fluid Macrophages Of Spinal Muscular Atrophy Patients Treated With Nusinersenmentioning
confidence: 99%
“…The presence of these inclusion-laden macrophages is now well-documented in patients receiving nusinersen and may be transitory as seen in our patients and by others. 7 However, the composition of the inclusions remains unclear. While it is tempting to assume the inclusions contain ASO particles, no definitive evidence confirms this.…”
Section: Unusual Inclusions In Cerebrospinal Fluid Macrophages Of Spinal Muscular Atrophy Patients Treated With Nusinersenmentioning
confidence: 99%
“…Although other basic parameters remained unchanged, 2 of 10 patients had activated lymphocytes and 6 patients had mononuclear phagocytic cells in CSF indicating induction of innate immunity either mediated by repeated lumbar puncture or by nusinersen's direct effect, which is still not understood. However, Gingele et al have demonstrated the presence of macrophage in CSF of nusinersen‐treated patients and that was not found in patients suffering from other disease and underwent repeated lumbar puncture (Gingele et al, ), signifying that nusinersen can be a cause for immune induction in patients over prolonged use. Additionally, since all patients do not equally respond to this therapy and the long‐term tolerability and safety of nusinersen are still unknown, investigations on experimental combination therapy are also reported (Pagliarini et al, ).…”
Section: Biomarker Identification For Adolescent and Adult Smamentioning
confidence: 99%